A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
(3x+1)=(2x+2) it's asking for work, but I don't know how. Please help
anonymous
 one year ago
(3x+1)=(2x+2) it's asking for work, but I don't know how. Please help

This Question is Closed

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0(3x+1)=(2x+2) 3x= 2x+1 x=1

mathstudent55
 one year ago
Best ResponseYou've already chosen the best response.1I assume you need to solve the equation for x. First step is to drop the parentheses. They are not needed. 3x + 1 = 2x + 2

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Thanks, but how do I get to it?

mathstudent55
 one year ago
Best ResponseYou've already chosen the best response.1Now you want all terms with x on the left side, so we subtract 2x from both sides.

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Alright 3x+1=2x+2 1X+1=x+2

mathstudent55
 one year ago
Best ResponseYou've already chosen the best response.13x + 1 = 2x + 2 2x 2x  x + 1 = 2 Now we have x + 1 = 2 We want x alone on the left side, so we subtract 1 from both sides: x + 1 = 2  1 1  x = 1 The answer is x = 1

mathstudent55
 one year ago
Best ResponseYou've already chosen the best response.1No, your last response is not correct. When you subtract 2x from both sides, there is no x left on the right side. 3x + 1 = 2x+2 2x 2x  x + 1 = 2

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Wait, what type of equation is this?

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Thank you for that little explanation. I haven't got into this type of math in a while and I don't remember some of the basics @mathstudent55

mathstudent55
 one year ago
Best ResponseYou've already chosen the best response.1Now that we have x = 1, we can check to see if the solution is correct. Take the original equation, (3x + 1) = (2x + 2), and replace x with our solution, 1. 3(1) + 1 = 2(1) + 2 3 + 1 = 2 + 2 4 = 4 Since 4 = 4 is a true statement, that means our solution, x = 1, is the correct solution.
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.